Еsтiматiоn оf dnа quаnтiту in diffеrеnт grоuрs оf мiсrооrgаnisмs wiтнin gеnетiс ноrizоns оf тне dаrк-grау sоil - A. D. Zhelezova; O. V. Kutovaya; V. N. Dmitrenko; A. K. Thakahova; S. F. Hohlov (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Molecular-biological methods permitted to study the structure of the microbial community in the profile of dark-gray soil (Luvic Retic Greyzemic Phaeozem) in Kashira district of the Moscow region. Microorganisms playing an important role in transformation of the soil organic matter are mainly concentrated in the topsoil and the major microbiological studies are related to this part of the soil profile. However, the study of the microbial community in the lower soil horizons is not only of theoretical but also practical interest in view of increasing the intensity of erosion processes. The method of quantitative polymerase chain reaction was used to estimate the DNA quantity of bacteria, archespores and micromycetes in horizons of the above soil. Under study was also the crotovina material at a depth of 80 cm. The highest DNA quantity of bacteria and archespores proved to be in the upper humus-accumulative horizon (9.6 × 108 and 9 × 107 copy/g of soil respectively). Their quantity was decreased downwards the profile, what is connected with changes in the physic-chemical conditions of soil. DNA of micromycetes was evenly distributed throughout the soil profile (5.4-9.4 × 107 copy/g). In the crotovina material the DNA content of different microorganisms groups was close to that in lower mineral soil horizons. This may be explained by water infiltration through the crotovina accompanying by eluviation of microorganisms in the period of soil wetting. The factors affecting the DNA amount of microorganisms are elementary soil processes including the biogenic-accumulative process in the upper soil horizons, clay-illuvial and humus-illuvial processes in the lower horizons of the dark-gray soil.